CD 121 - cultivar with flour characteristics for cookie baking - Marchioro,Volmir Sergio (2013)
CD 121 is indicated for wheat regions with the classification Value for Cultivation and Use 1 and 2, in the states of PR, SC and RS. The cultivar is tolerant to leaf rust, has good agronomic traits, flour suited for cookie baking and an average grain yield of 3.622 kg ha-1.